HYDROCHEMICAL CHARACTERIZATION OF A WATERSHED THROUGH FACTOR ANALYSIS - Invernizzi, Andre Luis; de Oliveira, Sonia Maria Barros (Águas Subterrâneas, 2004)
RESUMO Aplicou-se a análise fatorial aos dados hidroquímicos da bacia do Mogi-Pardo. Foram obtidos 3 fatores que deram conta de 60,01% da variabilidade total dos dados. O Fator 1 revela forte associação entre Na+, Li+, SO42-, CO32-, pH e condutividade, e uma correlação menor com F-, Cl- and B3+. Este fator representa a contribuição dos minerais evaporíticos, provavelmente da Formação Pirambóia. O Fator 2 é definido pelo ion Ca2+ que é fortemente correlacionado com Mg2+, Sr2+, HCO3- e a dureza. Ele representa a progressiva interação entre a água e a Formação Botucatu no sentido do fluxo, a partir da zona de recarga até a zona confinada pelas lavas basálticas. O Fator 3 agrupa Fe2+, Mn2+ and Zn2+, e é interpretado como devido à contribuição das águas dos solos. A projeção das amostras no diagrama F1 versus F2 permitiu uma boa sepração entre os grupos de águas de acordo com a localização na zona de recarga ou na porção confinada do aqüífero. ABSTRACT R-mode factor analysis was applied to hydrochemical data from the Mogi-Pardo watershed. Three factors, accounting for 60,01 % of the total data variability, were obtained. Factor 1 reveals strong associations between Na+, Li+, SO4 2-, CO32-, pH and conductivity, and a lesser correlation with F-, Cl- and B3+. It represents the flushing of evaporite minerals, probably from the Piramboia Formation. Factor 2 is defined by the Ca2+ ion which is strongly correlated with Mg2+, Sr2+, HCO3 - and hardness. It represents the progressive interaction between the water and the Botucatu Formation down the flow gradient, from the recharge zone to the zone confined by the basalt lavas. Factor 3 groups together Fe2+, Mn2+ and Zn2+ and is interpreted as the input of soil waters. Plots of samples on F1 versus F2 allowed a good separation of groups of waters according to their situation in the recharge area or in the confined portion of the aquifer.